Enhancing the Performance of Gen Z New Ventures Through Entrepreneurial Orientation and Social Media Adoption - Mega Noerman Ningtyas; Wening Patmi Rahayu; Agus Hermawan (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to investigate the impacts of entrepreneurial orientation and social media adoption on business performance, and the mediating role of social media adoption in the context of Generation Z entrepreneurs as new entrants. This study employed a quantitative approach with a survey and collected data from 68 Gen Z business owners in East Java, Indonesia. The data were analyzed using SEM-PLS. The results indicate that entrepreneurial orientation has a positive and significant effect on business performance. Similarly, social media adoption is found to significantly enhance business performance. However, the role of social media adoption as a mediating effect was not supported. These findings suggest that while both entrepreneurial orientation and social media adoption are important drivers of performance, social media has not yet functioned as a strategic mechanism linking entrepreneurial behavior to performance outcomes among new entrants. This contributes to the literature by highlighting the role of generational context and suggesting that strategic capabilities in utilizing digital tools are crucial for maximizing business performance.